Power, Culture and Situated Research Methodology Autobiography, Field, Text - Neumann, Cecilie Basberg (Springer International Publishing, 2018)
This book explores the extent to which our lives become an important underlying context for data production. Drawing on insights from Gestalt psychology, feminism and post-structuralism, it discusses how to situate yourself in the different phases of research.